2007
DOI: 10.1111/j.1469-7580.2007.00820.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an intestinal cell culture model to obtain smooth muscle cells and myenteric neurones

Abstract: This paper reports on the development of an entirely new intestinal smooth muscle cell (ISMC) culture model using rat neonates for use in pharmacological research applications. Segments of the duodenum, jejunum and ileum were obtained from Sprague-Dawley rat neonates. The cell extraction technique consisted of ligating both ends of the intestine and incubating (37 ºC) in 0.25% trypsin for periods of 30-90 min. Isolated cells were suspended in DMEM-HEPES, plated and allowed to proliferate for 7 days. Cell cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Accordingly, we used trypsin to dissociate the colonies into single cell suspensions, which disrupted polarity and enabled differential adhesion, a method we and others have used to purify primary cells [59]. As shown in Figure 2A, the resulting cells grew as dispersed monolayers rather than as colonies.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, we used trypsin to dissociate the colonies into single cell suspensions, which disrupted polarity and enabled differential adhesion, a method we and others have used to purify primary cells [59]. As shown in Figure 2A, the resulting cells grew as dispersed monolayers rather than as colonies.…”
Section: Resultsmentioning
confidence: 99%
“…To culture enteric neurons, Lobo et al showed that it is possible to extract just the desired portion of the intestine, followed by 30 min of trypsinization and incubation of all the detached cells (Lobo et al 2007). Even though this procedure is relatively fast and easy, it results in a cell culture that depicts the composition of the entire intestine and not just enteric neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The mixture was centrifuged at 1000 rpm for 10 min at 4°C, the pellet was resuspended in 10 ml of fresh media, and a differential adherence approach was used to selectively separate fibroblasts from SMCs. 33 Briefly, the cell mixture was placed in pre-warmed culture flasks for 20 min at 37°C, where fibroblasts adhered, and the suspension of non-adherent cells was placed in another pre-warmed culture flask whereby SMCs derived from the muscularis mucosae, circular layer, and longitudinal layer adhered. After 3 weeks in culture, SMCs were propagated in DMEM/ Nutrient Mixture F-12 Ham media containing l-glutamine, A/A, and SMC supplement pack (C-39363, PromoCell).…”
Section: Cell Culturementioning
confidence: 99%